Influencing incentives for precision agricultural technologies within European arable farming systems. Issue 93 (March 2019) - Barnes, A.P.; Soto, I.; Eory, V.; Beck, B.; Balafoutis, A.T.; Sanchez, B.; Vangeyte, J.; Fountas, S.; van der Wal, T.; Gómez-Barbero, M.
Highlights: Current adopters of precision agriculture are divergent from current non-adopters. First adopters are influenced by economic and informational interventions. Increasing adoption is constrained by scepticism towards economic returns. EU agricultural policy does not recognise complexity across domains to enable uptake.